SPATIO-TEMPORL ANALYSIS OF TERRORIST ACTIVITIES IN THE NORTH CAUCASUS - Ilya Pavlovich Suprunchuk (Наука. Инновации. Технологии, 2022)
This article proposes a spatio-temporal approach to the investigation of terrorist activities, based on the concept of territorial structures. It identifed three major groups of factors of terrorism: geopolitical, socio-economic and ethno-religious. The article describes the geographical features of terrorism in the North Caucasus over the past 20 years, determined by the place of the region in the development of terrorism in Russia. The dynamics of terrorist activities in the region - marked periods of its development, defned territorial changes have occurred. The author proposes a model of territorial structure of terrorism in the North Caucasus, which consists of three zones, differing in intensity and number of other parameters. Separately analyzed the regional peculiarities of terrorist activities in the North Caucasus on the basis of the collected statistical data.